Diagnostic sensitivity of SILVAMP TB-LAM (FujiLAM) point-of-care urine assay for extra-pulmonary tuberculosis in people living with HIV - Kerkhoff, Andrew D.; Sossen, Bianca; Schutz, Charlotte; Denkinger, Claudia M. (European clinical respiratory journal, 2020)
Tweetable abstract ERSpublications - click to tweetFujiLAM point-of-care rapid urine test for TB detects a large proportion of pulmonary and traditionally difficult-to-diagnose extra-pulmonary forms of TB in hospitalised patients with advanced HIV http://bit.ly/36Dl0Eo